Attitude control of spacecraft simulator without angular velocity measurement. (March 2019) - Malekzadeh, Maryam; Sadeghian, Hamid
Abstract: In this paper the attitude control of a spacecraft simulator using Reaction Wheels (RW) as the actuators is investigated. The main goal of the current study is to bring the RWs to the rest at the end of the maneuver without angular velocity measurement. A modified feedback linearization controller is applied by considering the Euler angles of the simulator as the output and the RWs angular momentums as the internal state variables. The stability of the proposed controller and the internal dynamics is analyzed using Lyapunov theory. Two modified sliding mode observers are designed to estimate the angular velocities of the spacecraft attitude control subsystem simulator. The proposed observers do not use the control input and the detailed knowledge of the model and thus it can be implemented easily. The global stability of the system is proved. The proposed controller and observers are finally evaluated numerically and experimentally on an attitude spacecraft simulator. Highlights: Bringing the reaction wheels to the rest at the end of maneuver without any extra actuator. The internal dynamics stability is analyzed by bringing the dynamics of the system in normal form. Two modified robust observers are designed in such a way that the model parameters and control input are not required for the formulation. The proposed controller and observers are implemented experimentally on a spacecraft attitude control simulator. The performance of the empirical studies and the computer simulations are compared.